2020
DOI: 10.1080/10717544.2020.1818881
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib-loaded CalliSpheres Beads for embolization in a rabbit VX2 liver tumor: characterization in vitro , pharmacokinetics and tumor response in vivo

Abstract: Apatinib mesylate is an oral antiangiogenic agent that can inhibit activation of vascular endothelial growth factor receptor-2 tyrosine kinase. However, its therapeutic use in liver cancer is restricted due to severe systemic toxicity. Our work aimed to construct apatinib-loaded CalliSpheres Beads (CBAPA) and investigate its application in transarterial chemoembolization (TACE) of liver cancer. The established stock solution containing 20, 40 or 60 mg apatinib were fully mixed with 100–300 μm CalliSpheres Bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…For example, Shi et al. prepared an “Apatinib-loaded CalliSpheres Beads” for embolization and examined the pharmacokinetics and tumor response in a rabbit VX2 liver tumor model ( 67 ). The strategy of this study is fundamentally different from these studies: these studies must use microspheres made of polymer materials (such as CalliSpheres Beads) to physically adsorb molecular targeted drugs, and the chemical properties of molecular targeted drugs affect the drug-amount carried by microspheres; and the drug-loaded microspheres obtained in these strategies are mainly the microspheres themselves, and the drug content is limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shi et al. prepared an “Apatinib-loaded CalliSpheres Beads” for embolization and examined the pharmacokinetics and tumor response in a rabbit VX2 liver tumor model ( 67 ). The strategy of this study is fundamentally different from these studies: these studies must use microspheres made of polymer materials (such as CalliSpheres Beads) to physically adsorb molecular targeted drugs, and the chemical properties of molecular targeted drugs affect the drug-amount carried by microspheres; and the drug-loaded microspheres obtained in these strategies are mainly the microspheres themselves, and the drug content is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The agents were physically adsorbed to the microspheres. As an example, the results from Shi et al, 2020 shown that prepared the Apatinib as loaded CalliSpheres Beads for embolization could achieved the good pharmacokinetics feature and tumor response in liver tumor model (115). However, the usage of the microspheres still has some shortcomings: the microspheres such as CalliSpheres Beads were made by the polymer materials and these polymer materials may not be biodegradable.…”
Section: Discussionmentioning
confidence: 99%
“…Donafenib has a similar chemical formula to sorafenib, 18 and both carry a positive charge (NH + ) ( Figure 1A ). Composed of polyvinyl alcohol hybrid hydrogel linked to sulfonate group, CBs are net-like spheres carrying negative charge, 19 , 20 allowing drugs charged positively for interaction. The DCBs characterizations were explored as described in the previous literature.…”
Section: Methodsmentioning
confidence: 99%